RELIGIOUS MODERATION AS A PRODUCT OF ISLAMIC TEACHINGS OF RAHMATAN LIL'ALAMIN AND ISLAMIC EDUCATION - Siti Kamilah; Zamroni Zamroni; Rita Sriayu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Religious moderation is an important implementation of the Islamic teachings of rahmatan lil'alamin, which prioritizes tolerance and balance, and rejects extreme attitudes in religious life. This concept positions Islam as a blessing for all nature and prioritizes social harmony in a pluralistic society. In the context of Islamic education, its role is very strategic in instilling the value of moderation through the development of an inclusive and dialogical curriculum and learning approach. This study examines the concept of religious moderation as a product of the Islamic teachings of rahmatan lil'alamin and the role of Islamic education in internalizing these values in students. Data were obtained through a literature review and analysis of the Islamic education curriculum. The findings indicate that Islamic education can shape the character of a moderate and tolerant young generation, while reducing the potential for radicalism and intolerance. Thus, religious moderation is not only a principle of Islamic teachings but also an important part of character development through Islamic education.